ANALISIS BIAYA DIFERENSIAL PER JENIS PRODUK DALAM UPAYA MENGOPTIMALKAN LABA PERUSAHAAN PADA PT. SISPUM SARANA GRAHA - Siska Yulia Weny (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The cause of the emergence of profit or loss from an entity requires the ability to analyze objects that generate profit or loss in a certain period. The object in question can be the type of product, the product itself, production activities, and organizational performance within the company. The purpose of this study is to analyze the role of differential costs per product type in an effort to optimize company profits. The methods used in this research are quantitative and qualitative methods. The result of this research is the analysis of profitability by type of product shows that even though there are symptoms of a decline in sales, the product (PF) is able to provide the third segment margin. Segment margin by product shows the product's ability to provide profit. If the segment margin is large, it means that the product is able to provide a large profit and vice versa, if the product is only able to provide a small profit, it means that the segment margin is small. Therefore. product (PF) is a product that is considered profitable. So this product needs to be maintained.